TECHNOLOGY INNOVATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE FIRST MIDDLE SCHOOL (SMP - Ahmad Jaelani; Agus Salim Mansur; Qiqi Yulianti Zaqiyah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
This article deals with Islamic Religious Education (PAI) learning technology innovation at the junior high school level. The focus of the problem studied is related to what is innovation, technology and how is PAI's learning technology innovation at junior high school level. The results showed that the form of PAI learning technology innovation at junior high school level included; educational innovation, technology, learning technology, development of learning technology, web-based learning (e-learning), as well as the internet as a source of learning with an approach to developing inquiry and discovery learning methods. The effectiveness of this learning technology innovation makes the subject matter more understood by students, because the material from teaching material is discovered and practiced by students themselves. While the response of students is very enthusiastic and positive. The weakness of this learning technology innovation is that there are obstacles in operating learning technology because not all students have a representative media in implementing technology-based learning (online).